Evaluación institucional universitaria en Europa y América Latina - Salvador Blanco, Laurentino (Revista Española de Pedagogía, 2018)
The article defines three institutional evaluation models (English, French and Dutch one) and revises some of the experiences in institutional evaluation fron Europe and Latin America trying to extract points in common as well as between them. We could say that, mostly, the projects of institutional evaluation plan at universities emerge promoted by universities themselves and are pushed by goverments inside the context of institutional improvements. Most of the governments put the control that implies the accreditation of universities to give the correspondent degrees. In generat terms, we could say that, the academic institutions put the stress improvements while the governments do the same with the control or accreditation of them. This is largely explained in the National Plan for Universities Quality Evaluation in progress at the time being in Spain and some ideas being considered for a better implantation of the plan.
Keywords: evaluación institucional; Europa; América Latina; Revista Española de Pedagogía